PENERAPAN METODE FUZZY INFERENCE SYSTEM TSUKAMOTO PADA SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMAAN BEASISWA - Fitria -; Suhendro Yusuf Irianto (IIB Darmajaya, 2016)
Fuzzy logic is one method to perform system analysis that contains uncertainty. Fuzzy logic mimics a human thinking way called reason, where reason can explain and identify things automatically. In this research used inference method of Fuzzy Tsukamoto system. The design of the system for obtaining output is carried out in stages (a) The establishment of the Fuzzy set, (b) Application of the implication function, (c) The composition of the rule, (d) the affirmation (Defuzzification). To assist the determination in determining a person who is eligible to receive a scholarship then required a decision support system. One method that can be used for Decision Support System is to use Fuzzy Inference System Tsukamoto.So the result of the selection is if the value Z = 70.78571, then the decision is Accepted with limitation if the received output value is 70-80 and if the reject between 0-60.This method is chosen because it is able to select the best alternative from a number of alternatives, in this case, the intended alternative is the right to receive the scholarship based on the criteria specified[6]. The research is done by finding the value of weight for each attribute then done the ranking process that will determine the optimal alternative, that is the best student. Keywords: Fuzzy Tsukamoto, Decision Support System (SPK), Scholarship Reception